Developing English Board Game to Improve Students’ Speaking Skill - Indah Nuraini; Husni Mubarok (JEELS (Journal of English Education and Linguistics Studies), 2025)
This research develops an English board game to improve students’ speaking skills. The aims of this research are 1) to find out the need for analysis of English board games, 2) to investigate their practicality, 3) to evaluate their feasibility, and 4) to examine their effectiveness. This research employed the ADDIE method, beginning with analysis, which revealed that students faced challenges in speaking skills due to conventional learning media. Then, the design phase focused on creating the media tailored to the student’s preferences and learning requirements; the development phase involved incorporating elements that would facilitate speaking practice, and the implementation phase provided the game in real-time. It facilitated speaking practice, and finally, the effectiveness phase was assessed using a T-test. Data was collected through observation, interviews, and questionnaires. These results suggest a significant improvement in students’ speaking skills through the use of innovative and engaging media. Further studies should focus on integrating online platforms and adapting the English board game to different levels of English proficiency.